School of Nepalese Architecture - Thapa, Shree Hari (Journal of Innovations in Engineering Education, 2019)
Architecture is an art of creation for the shelter of human beings. The shelter is called a secured place by the fierce animals, natural calamity, and with complete privacy. The school of architecture is distinguished in its use of construction material, skill, techniques, technology, form including the aspiration of the human being on the geographical strata. The technology and tradition of the construction of a building with certain forms and pattern are influenced by the climate, time, situation, and native construction material. Similarly, the migrants, traders, pilgrimage and travelers had transferred knowledge of tradition and technology with the principle of design philosophy from one place to another. The local or indigenous peoples, who lived or inhabit in the region with climate and geological strata, house form and pattern is varied due to the availability of indigenous construction material. The settlement pattern and the design philosophy of the houses in Nepal are geographically divided into three different regions due to its distinctive ways of construction.